Aplikasi Computer Vision pada Desain Batik Folklor Muara Jambi sebagai Upaya Inovasi Digital Berkelanjutan - Sri Rustiyanti; Wanda Listiani (Prosiding Seminar Nasional Ilmu Teknik, 2025)
This research aims to recontextualize the local wisdom embedded in the visual culture of the Muara Jambi Temple through the development of folklore-inspired batik motif designs. As a traditional Indonesian textile craft, batik serves not only functional purposes but alsp embodies profound cultural values and indigenous knowledge systems. Batik as a medium of cultural expression that invites multidimensional interpretaion within both practical and theoretical academic discourses. Its visual strength lies in the richness of colors, ornaments, and symbolic elements, which generate diverse interpretative meanings. These interpretations subsequently shape value systems that function as guiding principles in the everyday lives of Indonesian communities. The research used an experimental design method integrated with computer vision techniques to generate distinctive folklore batik motifs rooted in the cultural heritage of Muara Jambi, Sumatra. The research results are the creation of a Muara Jambi folklore batik motif that represents cultural expression, resilience, and continuity through the preservation of traditional patterns and environmentally conscious practices within the Jambi community. The transformation of motifs derived from artifacts from the Muara Jambi temple complex, serves as a primary source of inspiration for contemporary folklore batik design. The application of computer vision in the batik design process constitutes a form of sustainable digital innovation, facilitating the preservation, reinterpretation, and adaptive transformation of traditional visual heritage.